2017
DOI: 10.14198/jhse.2017.124.05
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a high-intensity interval training protocol based on functional exercises on performance and body composition in handball female players

Abstract: The aim of this study is to measure the impact of 8-week high-intensity interval training (HIIT) based on functional exercises on the following variables in handball female players: weight (kg), body mass index (BMI), % fat, jumping (cm), repeated sprint ability (RSA), aerobic capacity. Fourteen female players were randomly assigned either to an experimental group (GE, n=7) which would undertake a "mixed functional HIIT" (combining strength, coordination and plyometric exercises) before training sessions, or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(65 citation statements)
references
References 21 publications
(30 reference statements)
1
62
0
2
Order By: Relevance
“…All studies specified their eligibility criteria, similar baseline group, betweengroup comparisons, point measure and variability. None of the studies reported on allocation concealment, blind subject, blind therapist, blind assessor, or intention to treat analysis, except for three studies which described random allocation (Tomljanović et al, 2011;Alonso-Fernández et al, 2017;Yildiz et al, 2019), and only one study reported follow-ups (Oliver and Brezzo, 2009). Nevertheless, it is challenging to include blind subjects, blind therapists, and blind assessors as participants and assessors, since the included studies were exercise training interventions.…”
Section: Study Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies specified their eligibility criteria, similar baseline group, betweengroup comparisons, point measure and variability. None of the studies reported on allocation concealment, blind subject, blind therapist, blind assessor, or intention to treat analysis, except for three studies which described random allocation (Tomljanović et al, 2011;Alonso-Fernández et al, 2017;Yildiz et al, 2019), and only one study reported follow-ups (Oliver and Brezzo, 2009). Nevertheless, it is challenging to include blind subjects, blind therapists, and blind assessors as participants and assessors, since the included studies were exercise training interventions.…”
Section: Study Quality Assessmentmentioning
confidence: 99%
“…On the other hand, a new exercise training method that has recently received much attention to developing athletes' physical fitness is functional training (Feito et al, 2018). Several studies have confirmed that functional training can enhance speed (Tomljanović et al, 2011;Sander et al, 2013;Alonso-Fernández et al, 2017;Yildiz et al, 2019;Baron et al, 2020;Keiner et al, 2020), muscular strength (Oliver and Brezzo, 2009;Tomljanović et al, 2011;Elbadry, 2014;Cherepov and Shaikhetdinov, 2016;Keiner et al, 2020), power (Tomljanović et al, 2011;Alonso-Fernández et al, 2017;Yildiz et al, 2019;Keiner et al, 2020), balance (Oliver and Brezzo, 2009;Elbadry, 2014;Yildiz et al, 2019), body composition (Oliver and Brezzo, 2009;Tomljanović et al, 2011;Alonso-Fernández et al, 2017), agility (Tomljanović et al, 2011;Cherepov and Shaikhetdinov, 2016;Yildiz et al, 2019), flexibility (Yildiz et al, 2019) and muscular endurance (Oliver and Brezzo, 2009). Additionally, other research has discovered positive effects of functional training on physical fitness in football players (Oliver and Brezzo, 2009;Sander et al, 2013;Baron et al, 2020;Keiner et al, 2020), handball players (Elbadry, 2014;Alonso-Fernández et al, 2017), martial artists (Cherepov and Shaikhetdi...…”
Section: Introductionmentioning
confidence: 99%
“…In HICT, body weight is used for resistance, and it eliminates the need for equipment and facilities. For this reason, HICT exercises are often used in high‐intensity interval training (HIIT) which is also an optimal workout for improving metabolic and cardiovascular functions (Alonso‐Fernandez et al, 2017). Therefore, HICT is a time‐efficient strategy which facilitates training adaptation to a similar extent as competitive training (Martins et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, HICT is a time‐efficient strategy which facilitates training adaptation to a similar extent as competitive training (Martins et al, 2016). HICT is highly effective in team sports (Alonso‐Fernandez et al, 2017), most combat sports (Podstawski et al, 2016a), functional training such as cross‐fit and water sports (Claudino et al, 2018). Fan et al (2013) demonstrated that high‐intensity exercises performed for both less and more than 10 minutes decreased the body mass index and lowered the risk of obesity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation